Mutations in the substrate binding site of human heat‐shock protein 70 indicate specific interaction with HLA‐DR outside the peptide binding groove. Issue 2 (June 2014) - Rohrer, Karin M.; Haug, Markus; Schwörer, Daniela; Kalbacher, Hubert; Holzer, Ursula
Summary Heat‐shock protein 70 (Hsp70)–peptide complexes are involved in MHC class I‐ and II‐restricted antigen presentation, enabling enhanced activation of T cells. As shown previously, mammalian cytosolic Hsp70 (Hsc70) molecules interact specifically with HLA‐DR molecules. This interaction might be of significance as Hsp70 molecules could transfer bound antigenic peptides in a ternary complex into the binding groove of HLA‐DR molecules. The present study provides new insights into the distinct interaction of Hsp70 with HLA‐DR molecules. Using a quantitative binding assay, it could be demonstrated that a point mutation of amino acids alanine 406 and valine 438 in the substrate binding pocket led to reduced peptide binding compared with the wild‐type Hsp70 whereas HLA‐DR binding remains unaffected. The removal of the C‐terminal lid neither altered the substrate binding capacity nor the Hsp70 binding characteristics to HLA‐DR. A truncated variant lacking the nucleotide binding domain showed no binding interactions with HLA‐DR. Furthermore, the truncated ATPase subunit of constitutively expressed Hsc70 revealed similar binding affinities to HLA‐DR compared with the complete Hsc70. Hence, it can be assumed that the Hsp70–HLA‐DR interaction takes place outside the peptide binding groove and is attributed to the ATPase domain of HSP70 molecules. The Hsp70‐chaperoned peptides might thereby be directly transferred into the binding groove of HLA‐DR, so enabling enhanced presentation of the peptide on antigen‐presenting cells and leading to an improved proliferation of responding T cells as shown previously.